Pengaruh Kualitas Pelayanan, Suasana Toko Dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Toko Bangunan UD. Barokah, Buring, Kota Malang - Aurel Aini Auliya; Achmad Agus Prioyono; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of service quality, store atmosphere, and promotion on purchasing decisions at UD. Barokah (study on TB consumers. UD. Barokah Buring, Malang City). The method used is descriptive research analysis with quantitative data types. The sample in this study amounted to 80 respondents with the technique used in this study purposive sampling. The results of the study show that service quality, store atmosphere, and promotions have a significant effect on purchasing decisions. Service quality has a significant effect on purchasing decisions. Store atmosphere has a significant effect on purchasing decisions. Promotion has a significant effect on purchasing decisions. Keywords: Service Quality, Store Atmosphere, Promotions, And Purchasing Decisions